1995
DOI: 10.1056/nejm199511023331803
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Optic Neuropathy in Cuba — Clinical Characterization and Risk Factors

Abstract: The epidemic of optic and peripheral neuropathy in Cuba between 1991 and 1993 appears to be linked to reduced nutrient intake caused by the country's deteriorating economic situation and the high prevalence of tobacco use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(15 citation statements)
references
References 21 publications
2
12
0
1
Order By: Relevance
“…Large-scale outbreaks of peripheral neuropathy have been associated with food shortages and low intakes of animal fat and protein [23]. Similar to previously investigated outbreaks [4], [5], overt malnutrition was not present in this population, but multiple micronutrient deficiencies were identified. Of the malnutrition-related neurological disorders, peripheral neuropathy has been associated with several micronutrient deficiencies, including copper [24], chromium, pyridoxine (B6) [25] and cobalamin (B12) and thiamine (B1), which are most frequently reported among confined populations [26].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Large-scale outbreaks of peripheral neuropathy have been associated with food shortages and low intakes of animal fat and protein [23]. Similar to previously investigated outbreaks [4], [5], overt malnutrition was not present in this population, but multiple micronutrient deficiencies were identified. Of the malnutrition-related neurological disorders, peripheral neuropathy has been associated with several micronutrient deficiencies, including copper [24], chromium, pyridoxine (B6) [25] and cobalamin (B12) and thiamine (B1), which are most frequently reported among confined populations [26].…”
Section: Discussionsupporting
confidence: 82%
“…Outbreaks of optic and peripheral neuropathy, for which the identification of a definitive cause is challenging, have been reported in association with dietary inadequacies [4], [5]. Despite numerous reports of both cholera [6] and peripheral neuropathy [3] among internally displaced persons (IDPs), the epidemiological features of their concurrent outbreaks and their impact on mortality have not been previously described.…”
Section: Introductionmentioning
confidence: 99%
“…The Cuban optic neuropathy epidemic associated the use of tobacco, especially cigars, and malnutrition, to vision loss from an optic neuropathy. [48] Susceptible individuals who harbor the mitochondrial DNA mutations associated with LHON should be counseled to avoid smoking. Kirkman et al found that smoking significantly increased the risk of vision loss in patients harboring mutations for LHON.…”
Section: Optic Nervementioning
confidence: 99%
“…In another Latin American example, in 1994, the Cuban government issued a policy of supplementation of multivitamin pills containing 400 µg of folic acid to all the adult population, after an epidemic of optic neuropathy attributed to an ill-defined vitamin deficiency and possible food toxics [55]. In addition, as described below, since the mid-1980s Cuba has implemented a very successful program of prenatal detection of neural tube defects based on prenatal α-fetoprotein and ultrasound screening, followed by the option of terminating affected pregnancies.…”
Section: Prevention Of Congenital Anomaliesmentioning
confidence: 99%